Understanding the Impacts of Paid Maternity Leave on Women's Labor Market Outcomes - Lillian Bates; Oliver Hall; Pamela Jakiela (Institute of Labor Economics (IZA), 2023)
All OECD countries except the United States offer at least four months of paid maternity leave, and the average duration of mandated paid maternity leave has increased steadily from 1970 to the present. There is some evidence that paid leave policies above a certain duration negatively impact women's labor market outcomes. In order to estimate the effects of paid leave, we link data on 40 years of paid leave policy across 24 European countries to survey data using a birth-cohort panel. Following previous work, we show that conventional fixed effects estimation suggests a non-monotonic relationship between leave length and women's labor force attachment, with leaves of three months or less increasing women's labor force attachment while longer leaves reduce it. However, in our context, the putative positive impacts of short-duration maternity leaves on women's employment appear to be driven by negative weighting in fixed effects estimation, which is explained by the fact that all countries in our sample eventually adopt short-duration leave policies. Using a robust imputation-based estimator, we find that maternity leaves longer than three months negatively affect female employment and increase women's domestic work burden. Leaves longer than six months also reduce women's educational attainment and their propensity to raise children.
Keywords: D13; J16; J22; 330; European social policy; women's labor force participation; parental leave; gender; fertility; two-way fixed effects